Frequency of Incisional Hernia in Patients with Previous Open Abdominal Surgeries - Ashraf, Waqas; Rafiq, Muhammad Kashif; Rehman, Tahir Ur; Sultan, Babar; Khan, Yousuf Aziz (Indus Journal of Bioscience Research, 2025)
Background: Incisional hernia (IH) is a common complication following open abdominal surgeries, with multiple risk factors contributing to its development. Objectives: We conducted investigation to ascertain the incidence of incisional hernia and pinpoint related demographic, clinical and socioeconomic risk variables in patients who have a background of open abdominal operations. Methods: Over six months, this cross-sectional study was carried out in the Surgical Unit of Ayub Teaching Hospital, Abbottabad from 15th July 2024 to 15th January, 2025. Using non-probability consecutive sampling, 112 patients total, between the ages of 20 and 70, who had undergone open abdominal surgery were included. Collected were data on demographic factors, smoking status, steroid use, comorbidities, BMI and socioeconomic level. Under clinical examination, we detected the incisional hernia. Results: Patients with higher BMI had more incisional hernia; this was especially true for the obese category (23 instances) and among those with lesser socioeconomic level (25 cases). Male patients had 30 rather than 20 case incidence compared to female patients. Though not statistically significant, smoking (18 cases) and steroid usage (12 cases) revealed trends toward greater occurrence. Though they were present in more individuals with incisional hernia, comorbidities including diabetes and COPD did not achieve statistical significance. Conclusion: Though the study revealed patterns pointing to higher BMI, male gender, lower socioeconomic level, smoking and COPD may help to explain incisional hernia formation. Further extensive research is required to validate these conclusions and enhance preventative plans.